Assessment of Student leadership Training program based on Student Leaders Perceptions: Case of a Private Secondary School in Zimbabwe. (International Journal of Scientific Research and Management (IJSRM), 2022)
The purpose of this was to evaluated the effectiveness of Student Leadership training program carried out for the newly elected student leaders of a private secondary school in Zimbabwe. A qualitative descriptive case study was used in this study. Ten 10 student leaders were purposively selected from a total of 24 student leaders. In-depth interviews were used to solicit the student leaders’ perceptions on the effectiveness of the student leadership training offered to the newly elected student leaders. Data collected was analysed using thematic Analysis. Findings of the study indicate that the student leadership program was deemed effective as it became an eye opener for most of the student leaders as it helped some to change their attitudes for better. The major strengths of the training program that were highlighted include that firstly the timing was very appropriate, coming soon after the installation and inauguration of the new leaders, before they assumed duties so they could be adequately equipped so as to avoid making blunders. Secondly, the training included team building activities and thirdly, that it was grounded on Christian principles such as honesty, integrity and Commitment to serve and uphold the school rules in an exemplary way. This equipped the budding leaders with key leadership skills and competencies such as interpersonal skills, effective communication skills, decision making strategies, problem solving skills as well as collaborative skills. Most participants opined that they got to understand their duties and responsibilities better and could feel confident to function as liaison between student body and faculty. On the other hand, the student leadership training had a major limitation of time constraint. Hence some of the topics were scantly covered and others such as issues of punishment were not covered at all. In conclusion, student leadership training should be considered seriously as an essential training not only of student leaders but as an opportunity to nurture and groom budding leaders for tomorrow. The study recommends that in future, the training could be more effective if it is carried out for 2-3 consecutive days of if it is split into 2 distinct phases, thus allowing for more interactive team building activities.